2019
DOI: 10.3889/oamjms.2019.760
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal Activity of Ketapang Leaf Fraction (Terminalia catappa L) on Aedes aegypti Instar III

Abstract: BACKGROUND: Mosquito control is essential in preventing mosquito-borne diseases. Natural substances originated from plants possessed the great potential of insecticidal properties, the resistance occurs at a slower rate compared to the synthetics, with less toxicity to other living creatures. AIM: This study aimed to identify the fraction of ketapang leaf (Terminalia catappa L) with larvicidal activity on Aedes aegypti instar III larvae, the concentration of ketapang active leaf fraction comparable to te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The larvicidal mechanism of tannins is related to their ability to inactivate adenosine, enzymes and cell proteins 46,47 . Hydrolyzed tannins are usually amorphous compounds, hygroscopic, yellow-brown in colour and soluble in water (boiling water) to form colloidal solutions instead of natural solutions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The larvicidal mechanism of tannins is related to their ability to inactivate adenosine, enzymes and cell proteins 46,47 . Hydrolyzed tannins are usually amorphous compounds, hygroscopic, yellow-brown in colour and soluble in water (boiling water) to form colloidal solutions instead of natural solutions.…”
Section: Resultsmentioning
confidence: 99%
“…The interaction of tannins with proteins is characteristic and depends on the structure of the tannins 48,25 . Some tannins have been shown to have an activity to inhibit reverse transcriptase and DNA topoisomerase enzymes 46 . Tannins bind to polysaccharides and are soluble in water.…”
Section: Resultsmentioning
confidence: 99%
“…The preliminary test exhibited that water-ethanol fraction possessed the highest larvicidal activity on Ae. aegypti larvae with larval death of 96.67% at 2000 ppm concentration (Redo et al, 2019). The effect of aqueous, ethanol and acetone extracts of Terminalia catappa leaves against the larvae and pupae of Aedesa egypti mosquito was studied.…”
Section: Effect Of Hot Water Bark Extractmentioning
confidence: 99%
“…The results of this study showed 100% mortality of Aedes aegypti larvae at a concentration of 2%. According to another study, Redo et al, (2019) said that the larvicidal activity of the water-ethanol fraction of ketapang leaves at a concentration of 1800 ppm was comparable to temephos. Another study regarding ketapang leaf extract which was tested on Aedes aegypti larvae showed an LC50 value of 166.00 ppm (Unnikrishnan, 2014).…”
Section: Introductionmentioning
confidence: 99%